Pseudogramma polyacantha complex (Serranidae, tribe Grammistini): DNA barcoding results lead to the discovery of three cryptic species, including two new species from French Polynesia - Williams, Jeffrey T.; Viviani, Jeremie (Zootaxa, 2016)
The Pseudogramma polyacantha species complex was found to harbor cryptic taxonomic diversity with three similar, but genetically divergent, species previously hidden in the complex. The true Pseudogramma polyacantha occurs from French Polynesia to South Africa and has modally 19 (many with 20) segmented dorsal-fin rays, modally 16 segmented anal-fin rays, a relatively short lateral line, no dermal flap or small tentacle dorsally on eye, and extensive scalation on the interorbital, suborbital and dentary. Pseudogramma brederi (previously synonymized with P. polyacantha) is recognized as a valid species occurring from Hawaii to Mauritius and having modally 21 segmented dorsal-fin rays, modally 17 segmented anal-fin rays, a relatively long lateral line, no dermal flap or small tentacle dorsally on eye, and relatively well-developed scalation on the interorbital, suborbital and dentary. Pseudogramma galzini n. sp. is described as a new species known only from French Polynesia and having modally 22 segmented dorsal-fin rays, modally 17 segmented anal-fin rays, a relatively long lateral line, no dermal flap or small tentacle dorsally on eye, and limited scalation on the interorbital, suborbital and dentary. Pseudogramma paucilepis n. sp. is described as a new species known only from French Polynesia and having 20 segmented dorsal-fin rays, modally 16 segmented anal-fin rays, a relatively long lateral line, no dermal flap or small tentacle dorsally on eye, and relatively reduced scalation on the interorbital, suborbital and dentary. A mtDNA COI analysis including all available Pseudogramma sequences shows well-supported genetic divergence between the two new species and among congeners.